Customary Marriage and Its Implementation in the Life of People in Batanghari, Jambi Province: According to Islamic Law - Mubarik, Mubarik; AM, Suhar; Ulum, Bahrul (PT. Riset Press International, 2024)
In carrying out weddings, the Batanghari people carry out ceremonies according to traditions inherited from generation to generation from their ancestors, even though the majority of the Batanghari people adhere to the Islamic religion. However, in the implementation of wedding ceremonies, some traditions are still considered inconsistent with Islamic teachings, which in turn becomes a problem, namely that customs/traditions take priority over the Shari'a. As a religious society and the majority adhere to the Islamic religion, the values that dominate the wedding ceremony procession should be the Islamic teachings that they adhere to. These concepts will be researched about the traditions of the Batanghari community and Islamic teachings, especially regarding the process of traditional ceremonies at weddings. The method used is qualitative, with data collection techniques in the form of observation, interviews, and documentation. The results of this research are: (1) The process of implementing customs that apply in marriages in the people of Batanghari Regency is carried out comprehensively and systematically in nine series, the sequence of which includes caring for single children and girls, choosing a mate, negotiation period, handing over customary delivery. , the wedding ceremony, the day of anchoring the lek, the handover between the bride and groom, the teaching and reprimanding of the bride's sapo, and the iwa. (2) The philosophical basis of the existence of marriage customs and their implementation as a crystallization of the values upheld by the people of Batanghari Regency emerged due to several factors, namely the existence of harmony between customs and Islamic law, the formation of a community which supports the Jambi customary system, the role of LAM. (3) The perspective of Islamic law regarding the activities that take place in the marriage customs of the people of Batanghari Regency is in harmony with Islamic values. However, minor specific aspects in particular series experience expansion and even conflict with Islamic law.